PENANGANAN PENGUNGSI ROHINGYA DI INDONESIA: HANDLING OF ROHINGYA REFUGEES IN INDONESIA - Mylova, Rezha Willy Putra; Naufal, Muhammad; Justinar, Jun (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2024)
Indonesia, as an archipelagic country with a Muslim majority population, has received Rohingya refugees in recent years. This article highlights Indonesia's response to the Rohingya humanitarian crisis, focusing on refugee policies and practices at the national level. This research is a normative legal research that includes research on legal principles with descriptive narratives. This research uses secondary and primary data as its main sources to support the findings. A comparative analysis will compare Indonesia's approach with other countries in the region, such as Malaysia and Thailand. The study shows that the three countries have not yet become parties to the 1951 Convention and/or the 1967 Protocol relating to the Status of Refugees, so the handling of Rohingya refugees in the three countries is handed over to the UNHCR. Thailand and Malaysia often detain refugees because they are illegal migrants. Indonesia, in handling Rohingya refugees, depends on assistance from donations from international organizations and other countries. This does not provide a long-term solution, so a comprehensive approach is needed in handling Rohingya refugees in Indonesia. The principle of non-refoulement binds all countries even if they are not parties to the 1951 Convention because this principle has become customary international law with a jus cogens character.